Iceland : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2013)
This Selected Issues paper analyses the impact of a potential rebalancing of Icelandic residents' investment portfolios as capital controls are lifted. It applies optimal portfolio theory to calculate the potential rebalancing toward foreign assets, and then makes an estimate of the cumulative impact on the balance of payments and international reserves. Conclusions for the authorities' capital account liberalization strategy are drawn. This paper also measures the potential budgetary savings from improving the efficiency of public spending in health and education in Iceland. A Data Envelopment Analysis is used to estimate an efficiency frontier by comparing across Organization for Economic Cooperation and Development countries the transformation rates of public spending into valuable social outcomes.